Evaluasi Tata Kelola TI Menggunakan Framework COBIT 5 Studi Kasus STMIK Primakara - Marciano Risky Fradinata; I Gede Juliana Eka Putra; I Nyoman Yudi Anggara Wijaya (Universitas Pendidikan Ganesha, 2021)
STMIK Primakara is a Technopreneurship campus who have a vision to produce IT Scholar with entrepreneurial mentality. However, to achieve that, STMIK Primakara need to manage the IT Government to support the academics and non-academics environment around the students until graduates are controlled by department of IT Development and Implementation (PPTI). The researcher will evaluates the capability level of IT Governance in STMIK Primakara and provide recommendations for the gap between the performance in domain process APO03, APO04, and BAI01 using quantitative and qualitative methods. Moreover, the researcher will use survey, interview, and document studies for the data required. The results of this research shows the average of capability level in domain process APO03, APO04, and BAI01 are partially achieved. Therefore, to fill the gap between STMIK Primakara current capability level and expected capability level, recommendation have been given by the researcher to create an improvement regarding to STMIK Primakara IT Governance.